Comparing 0.5% Bupivacaine versus 0.5% Levobupivacaine for peribulbar anaesthesia in cataract surgery - Fanai, Vanlalruati; Lalramthara, Israel; Vanlalhruaii (Student's Journal of Health Research Africa, 2024)
Background: The choice of drug used in the anaesthesia affects the overall outcome of cataract surgery, regarding patient satisfaction and adverse effects. Objectives: This study aimed to compare the efficacy and tolerability of levobupivacaine and bupivacaine in anaesthesia for cataract surgery. Materials and Methods: This was a double-blinded randomized study conducted in the operation theatre of Zoram Medical College for a year. The patients who were to undergo cataract surgery were considered for this study. They were divided randomly and were evaluated for the efficacy and safety of the drugs under study. The data obtained was compared statistically. Results: The akinesia score of the bupivacaine group at 10 minutes was 0.24±0.14 and for the levobupivacaine group it was 0.25±0.34. The patient’s satisfaction score in the bupivacaine group was 8.2±0.34 and in the levobupivacaine group, it was 8.4±0.21. The surgeons rated the quality of the motor block, the bupivacaine group had an average of 7.23±0.42 and for levobupivacaine, the average was 7.88±0.32. The results of both groups are comparable. Conclusion: The motor and sensory blockade for cataract surgery can be achieved with bupivacaine and levobupivacaine with similar efficacy and tolerance.z Recommendation: Levobupivacaine should be used as a local anaesthetic in patients with systemic disease to improve the outcome of the surgery.